Schelerowska kategoria resentymentu w świetle sporów o sekularyzację Zachodu - Banach, Wiesław (Człowiek i Społeczeństwo, 2022)
The aim of the article is to verify the category of ressentiment developed by Max Scheler in the light of disputes about the sources and causes of secularization. The category of ressentiment is one of the most important subjects of the author’s scientific reflection, being an expression of his particular interest in the functioning of the world of values. On the other hand, the processes of secularization, which have become visible in Western societies in recent decades, are understood here as the result of a decline in interest in religious issues and the disappearance of references to the broadly understood supernatural world. The key issues concern the extent to which the phenomenological conceptual apparatus developed by Scheler can serve today as an effective tool for a fuller understanding of the essence of contemporary disputes over the secularization of the West. Thus, it seems possible to assess the topicality of Scheler’s approach to the world of values as a timeless model and point of reference in research on the changing social reality.